INTERNALISASI NILAI-NILAI KRISTIANI DALAM PEMBELAJARAN PENDIDIKAN AGAMA KRISTEN BAGI PEMBENTUKAN KARAKTER PESERTA DIDIK DI SD INPRES TATELU RONDOR - Marsia Rumimpunu (MATA GURU: Jurnal Pendidik dan Tenaga Kependidikan, 2026)
This research aims to analyze the internalization of Christian values in Christian Religious Education learning at SD Inpres Tatelu Rondor. The research employed a qualitative method with a descriptive-analytic approach. Data were collected through observation, interviews, and literature study. The findings indicate that the process of internalizing Christian values at SD Inpres Tatelu Rondor takes place through spiritual learning activities and habituation programs implemented in the school environment. These activities include routine practices such as daily prayer, participation in religious learning, and the development of disciplined and respectful behavior in accordance with Christian teachings. Through these processes, students are expected to understand and apply Christian values in their daily lives. However, the implementation has not yet been fully effective, as the application of these values in students’ daily behavior remains inconsistent and not yet deeply rooted. This condition indicates that the internalization process still requires continuous reinforcement, guidance, and evaluation so that the values taught can be more effectively integrated into students’ character formation.